The Effects of Laser Marking and Symbol Etching on the Fatigue Life of Medical Devices. (7th April 2013) - Ogrodnik, P. J.; Moorcroft, C. I.; Wardle, P.
Abstract : This paper examines the question;" does permanent laser marking affect the mechanical performance of a metallic medical component?" The literature review revealed the surprising fact that very little has been presented or studied even though intuition suggests that its effect could be detrimental to a component's fatigue life. A brief investigation of laser marking suggests that defects greater than 25  μ m are possible. A theoretical investigation further suggests that this is unlikely to cause issues with relation to fast fracture but is highly likely to cause fatigue life issues. An experimental investigation confirmed that laser marking reduced the fatigue life of a component. This combination of lines of evidence suggests, strongly, that positioning of laser marking is highly critical and should not be left to chance. It is further suggested that medical device designers, especially those related to orthopaedic implants, should consider the position of laser marking in the design process. They should ensure that it is in an area of low stress amplitude. They should also ensure that they investigate worst-case scenarios when considering the stress environment; this, however, may not be straightforward.